Inhalation Exposure of Organophosphate Pesticides by Vegetable Growers in the Bang-Rieng Subdistrict in Thailand. (28th December 2009) - Jaipieam, Somsiri; Visuthismajarn, Parichart; Siriwong, Wattasit; Borjan, Marija; Robson, Mark G.
Abstract : This study investigated inhalation exposure to organophosphate pesticides (OPPs) and evaluated the associated health risks to vegetable growers living in the Bang-Rieng agricultural community. Air samples were collected by using personal sampling pumps with sorbent tubes placed in the vegetable growers' breathing zone. Samples were collected during both wet and dry seasons. Residues of organophosphate pesticides, that is, chlorpyrifos, dicrotofos, and profenofos, were analyzed from 33 vegetable growers and 17 reference subjects. Results showed that median concentrations of OPPs in air in farm areas were in the range of 0.022–0.056 mg/m 3 and air in nonfarm areas in the range of <0.0016–<0.005 mg/m 3 . The concentration of the three pesticides in the vegetable growers was significantly higher than that of the references during both seasons. The results also indicate that the vegetable growers may be at risk for acute adverse effects via the inhalation of chlorpyrifos and dicrotofos during pesticide application, mixing, loading, and spraying. It is suggested that authorities and the community should implement appropriate strategies concerning risk reduction and risk management.